Public relations writing and media techniques - Wilcox, Dennis L.; Reber, Bryan H. (Pearson Education, 2013)
"Public Relations Writing and Media Techniques is the most comprehensive and up-to-date public relations writing text available. With real-world examples of award-winning work by PR professionals, this new edition continues to help students master the many techniques needed to reach a variety of audiences in today's digital age. The text thoroughly integrates new communication technologies--the Internet, Webcasting, etc.--and shows students the many techniques currently in use to reach a variety of audiences. Clearly written and well-organized, this book emphasizes the nuts and bolts of writing, producing, and distributing public relations materials through traditional and social media. The author provides step-by-step procedures illustrated by examples from actual campaigns to engage today's students. This text also serves as an invaluable resource for public relations practitioners in the field."